Evaluation of Worker Exposure to Airborne Dust in Cotton Ginneries - Arude, V G; Shukla, S K; Manojkumar, T S (Journal of Agricultural Engineering, 2007)
Airborne dust in cotton ginneries is a nuisance as well as a potential respiratory hazard. The workers in ginneries are subjected to vagaries of airborne dust pollution. Exposure to dust causes cough, cold, fever, breathing difficulties and may even lead to lung disorders if exposed for long term. Dust concentration in mg/ mÂ³ of PM 2.5 µm and PM 10 µm was measured at different workstations. Time weighed average (TWA) of airborne dust of PM 2.5 and PM 10 was found up to 2.30 and 3.75 mg/mÂ³ respectively in conventional ginneries. In automatic ginneries, workers are exposed to TWA of airbome dust levels of PM 2.5 and PM 10 up to 0.20 and 0.58 mg/mÂ³, respectively. The workers in all types of ginneries are exposed to dust concentrations above the permissible limits in all workstations. The thoracic dust and respirable dust concentration levels were observed above the permissible limits in all the workstations. Workers employed in automatic ginneries are comparatively less exposed to airborne dust than conventional and semi-automatic ginneries. Workers stationed at press house, pala house and at lint opener are subjected to higher levels of airborne dust.